Toward classification-based sustainable revitalization: Assessing the vitality of traditional villages. (May 2022) - Liu, Sheng; Ge, Jian; Bai, Ming; Yao, Min; He, Linying; Chen, Ming
Abstract: Due to different capacities for protection and development, the vitality of traditional villages (VTV) in China varies to a great degree. However, the current classification-based sustainable revitalization strategies still lack an up-to-date vitality assessment. Based on the essential requirement of sustainable revitalization, this study defines the VTV as an integrated capacity to protect and develop and establishes an assessment index system from these two aspects. We also adopt the AHP method to determine suitable index weights for the case area and develop models to quantitatively assess vitality and vitality equalization for a large sample of universal traditional villages in the prefecture-level city. The research conducts the vitality evaluation of 148 traditional villages in Lishui, Zhejiang Province. It is found that the method can also analyze the vitality features of each grade from the spatial distribution and the disadvantaged indicators. The VTV assessed in this study was verified to be robust by the correlation test with the number of Point of Interest. Thus, the method is effective and may contribute to traditional villages' sustainable revitalization by providing the basis for classifying the policy-making and checking the revitalization effectiveness. Highlights: A practical assessment to quantify the vitality of a large sample of traditional villages. Indexes from both protection and development are combined to form a vitality model of traditional villages. Vitality equalization between protection and development is analyzed for its correlation with vitality value. Features of vitality values, spatial distributions, and disadvantage vitality indexes are identified within vitality grades. This method may contribute to appropriate policy-making for classification-based sustainable revitalization.